Acral lentiginous melanoma of the finger. Case report. - Orozco - Bobadilla , I-; Berumen, B. R; Mozqueda - Medina J. I, J. I; Moran - Martínez , J. (Revista de Ciencias Médicas Torreón, 2026)
Acral lentiginous melanoma (ALM) is a subtype of cutaneousmelanoma that primarily affects the palms, soles, andsubungual regions. We present the case of a 60-year-old malewith a history of smoking (with a non-significant pack-yearindex), active alcohol use since youth, and type 2 diabetesmellitus (diagnosed6years prior and treated withglimepiride, metformin, and insulin glargine); his remainingmedical history was unremarkable. He presented with apigmented nail disorder that had been evolving forapproximately 10 months, prompting him to seek adermatology consultation. Upon specialist evaluation, asuspected diagnosis of a malignant pigmented nail lesion wasestablished, and a biopsy protocol was initiated. In thispatient, the relatively early identification of the lesionallowed for diagnosis at a localized stage, with favorablehistopathological characteristics and the prospect ofconservative management of the digit.
Keywords: Acral lentiginous melanoma, cancer, biopsy